Is there stock market efficiency in Malaysia? - Sui Suyin, Crystal (2007)
This study is tests the Malaysian stock exchange, the Kuala Lumpur Stock Exchange (KLSE) for any evidences of efficiency. The approach to carrying out the tests is discussed in careful detail whilst still considering the other aspects of the study. The Efficient Market Hypothesis is explained in detailed as well a discussion on the vast debate concerning the EMH, which includes literature that support and do not support the concept of an efficient market. This debate is situated vitally around the issues of the EMH in which many researchers have found anomalies that exists in markets and therefore some conclude that markets are just not able to be efficient whilst others draw on other explanations which involve human behaviour (bringing about Behavioural Finance). Having obtained an understanding of the EMH and its issues, the background of the Malaysian market is brought into the study to later enlighten the results. This brings about the different stock market efficiency tests and previous studies done on stock market efficiency. Following this is the critical data analysis in which 3 quantitative tests were carried out to determine whether the KLSE is efficient. Despite the majority of previous literature indicating that the KLSE is inefficient, this study found the KLSE efficient with slight divergences from the EMH, which also supports a few previous studies that were the few that did not obtain data from the Asian Financial Crisis period. Therefore, a conclusion was made that the KLSE is overall, efficient; however, limitations were also noted to warn of the biases inherent in this study and in any model.